Fundamentos da filosofia moral de Peter Singer - Oliveira, Anselmo Carvalho de (2013)
This research aims to reconstruct and explain the argument proposed by Peter Singer to justify the principle of equal consideration of interests (PECI). The PECI is the basic normative principle according to people should consider the interests of all sentient beings affected when somebody taking a moral decision. It is the join that Singer proposes between universalizability and the principle of equal consideration of interests that constitutes a compelling reason to justify it. The universalizability requires to disregard the numerical differences, putting yourself in other people s shoes, and to consider preferences, interests, desires and ideals of those affected. Singer joins universalizability to normative principle and molds the form and content of his theory. The first chapter introduces the discussion will be developed in this essay. The second chapter deals the historical and philosophical viewpoint from which Singer starts his studies. The third chapter is about the Singer s critiques of naturalism, intuitionism, relativism, simple subjectivism and emotivism. The fourth chapter exposes the design of universal prescriptivism proposed by R. M. Hare. The universal prescriptivism indicates, in the Singer s viewpoint, a consistent way to create the join between the universalizability and PECI. It highlights also the criticism designed by J. L. Mackie and Singer himself to universal prescriptivism. The second part of this chapter shows briefly some of the main points of the classical conception of utilitarianism and its possible relationship with the theory of Singer. The fifth chapter introduces the Singer s thesis about the origin of ethics and the universalizability as a feature necessary to the point of view of ethic, and the way which this argument is developed to form the PECI. The sixth chapter exposes the main distinctions that characterize the PECI. Finally the seventh chapter provides a discussion about the reasons highlighted by Singer for one who wants orient his life according to the standpoint of ethics. This structure allows explaining the main ideas of the author concerning the theoretical foundations of his moral philosophy